P300 Event-Related Potentials Mediate the Relationship Between Child Physical Abuse and Externalizing Behavior - Cui, Naixue; Raine, Adrian; Connolly, Cynthia A.; Richmond, Therese S.; Hanlon, Alexandra L.; McDonald, Catherine C.; Liu, Jianghong (Frontiers in Psychology, 2021)
The psychophysiological mechanism linking early childhood experiences to behaviour problems remains unclear. This study aimed to examine the association of child physical abuse with P300 even-related potentials (ERP), and to test the mediating effect of P300 amplitude and latency in the relationship between child physical abuse and externalizing behaviors. Cross-sectional secondary data were obtained from 155 children (55.5 % boys, mean age: 11.28±0.57 years) who participated in the China Jintan Child Cohort Study. The following data were obtained in 2013: maternal and paternal physical abuse, externalizing behaviors reported by child, mother and teacher, and P300. Additionally, parents and teachers reported child externalizing behaviors in preschool in 2007. P300 were recorded during a standard novel auditory oddball task. Path analysis shows that after controlling for child sex, socioeconomic status, living environment, IQ, and child externalizing behavior in preschool, children exposed to maternal physical abuse exhibited increased novelty P300 amplitude, which links to more externalizing behavior. Novelty P300 amplitude partially mediated the relationship between maternal physical abuse and externalizing behavior. These findings are the first to document the partial mediating effect of P300 amplitude on the abuse-externalizing relationship and are consistent with the view that physical abuse affects the attention bias to novel cues that likely places them at increased risk for the development and maintenance of externalizing behavior.